Perbandingan Lembaga Anti Korupsi Di Indonesia Dan Malaysia - Irawati, Ade Lusy; Dompak, Timbul; Khairina, Etika (LPPM Universitas Putera Batam, 2024)
This research examines the comparison of anti-corruption agencies in Indonesia and Malaysia as a response to the detrimental global issue of corruption, which affects social, economic, and political spheres. Using the Systematic Literature Review (SLR) methodology, data were gathered through searching for relevant articles and journals. The Corruption Eradication Commission (KPK) of Indonesia, established in 2003, plays a crucial role in combating corruption in Indonesia, with main tasks including investigation, prosecution, and preventive functions. Meanwhile, the Malaysian Anti-Corruption Commission (MACC), formed in 2009, is an independent agency with a broad mandate to investigate and prosecute corrupt practices. Although these agencies have different roles, both aim to enhance transparency, accountability, and effectiveness in enforcing anti-corruption laws. This study also highlights the challenges and changes in the monitoring systems and the evolution of anti-corruption agencies in both countries, providing a comprehensive overview of anti-corruption efforts in Indonesia and Malaysia.